Sources of Output Growth of the ICT Sector in Vietnam - Thi Viet Duc, Dang; Huyen Linh, Dang (Journal of Reviews on Global Economics, 2020)
Vietnam has early set the strategy to develop ICT as the enabler for social-economic development and the Vietnamese ICT sector has grown significantly over the past 20 years. This paper analyses the development of the ICT sector by examining the sources of output growth and the structural changes in two periods of 2007-2012 and 2012-2016. The decomposition results show that the growth of the ICT manufacturing sector is attributed to export in both periods. However, the ICT manufacturing export was mainly based on components import; the sector neither could make any technological progress nor could manufacture products for import substitution. The ICT media and content sector’s growth was primarily due to technology advancement in 2007-2012 which led to the household demand-based development in the period 2012-2016. The ICT services sector shifted from primarily served government to household demand while technology was also significantly improved. The results of decomposition analysis are consistent with the macroeconomic situation as well as the ICT policies that the Vietnamese government has implemented over the past years. The paper points out the achievements and limitations in the ICT development policies and suggests directions for ICT policymakers in Vietnam in the coming period.